Riverine Flooding and Landfalling Tropical Cyclones Over China. Issue 3 (28th February 2020) - Yang, Long; Villarini, Gabriele; Zeng, Zhenzhong; Smith, James; Liu, Maofeng; Li, Xiang; Wang, Lachun; Hou, Aizhong
Abstract: Riverine flooding associated with landfalling tropical cyclones (TCs) in the western North Pacific basin is responsible for some of the most severe socioeconomic losses in East Asian countries. However, little is known about the spatial and temporal patterns of TC flooding and its climate controls, which constrain the predictive understandings of flood risk in this highly populated region. We provide a climatological characterization of TC flooding over China based on an exceptional network of stream gauging stations across the entire country. The most extreme floods in central and northeastern China are associated with TCs despite infrequent TC visits in these regions. Temporal variations in TC flooding demonstrate a mixture of controls tied to surface temperature anomalies in the northern hemisphere. The established links between TC flooding and climate controls present a potentially predictive tool of TC flood risk over China and other East Asian countries under future climate conditions. Plain Language Summary: Riverine flooding associated with landfalling tropical cyclones is responsible for some of the most severe socioeconomic losses all around the globe. This is a particularly critical issue for East Asian countries that lie on the margin of western North Pacific, the most active ocean in generating tropical cyclones. In this study, we investigate spatial and temporal variations of riverine flooding triggered by landfalling tropical cyclones across China. Our results show that the most extreme floods in central and northeastern China are associated with tropical cyclones, even though very few tropical cyclones affect this area. Surface temperature anomalies in both the Pacific and Atlantic regions determine the number of generated tropical cyclones, spatial pattern of tracks, and moisture transport. These combined effects, which can be well depicted using selected climate indices that represent large‐scale variability of the Earth's system, lead to temporal variations in the total number of flood peaks triggered by landfalling tropical cyclones across China. We establish relationships between these climate indices and the number of flood peaks induced by tropical cyclones over China and its subregions. These relationships can be used to project flood risk associated with these storms for other East Asian countries under a future climate. Key Points: Synchronized seasonality of rainfall and TC frequency plays a role in determining severe TC flood risk in central and northeastern China High TC flood risk in China is tied to combined temperature anomalies in central tropical Pacific, western North Pacific and north Atlantic We highlight challenges of potentially predictive tools of flood risk across China